The Law of Maninggian Janjang against Perpetrators of Adultery from Saddu al-dzari’ah's Perspective - Sudarman, Revoranda; Azwar, Zainal (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
The practice of